Towards Musical Interaction: Sam Hayden's Compositions for E-Violin and Computer. - Hayden, Sam; Kanno, Mieko (Contemporary Music Review, 2013)
This paper documents the evolution of the project on musical interactivity between electric violin and live computer processing (using Max/MSP), carried out by composer Sam Hayden in collaboration with violinist Mieko Kanno. Hayden's ‘schismatics’ composed in 2007, involved a standard performance paradigm of a fixed notated part for the e-violin with sonically unfixed live computer processing. This first version was more reactive than interactive, having little internal relationship between the two ‘performers’ beyond an initial e-violin ‘action’ causing a computer ‘event’. Extensive revisions in 2010 aimed at achieving (1) a more interactive performance situation and (2) a subtler and more ‘musical’ relationship between live and processed sounds. This was realized through the introduction of sound analysis objects, in particular machine listening and learning techniques developed by Nick Collins, leading to a new work, ‘Adaptations’ (2011) which has taken the concept of performance with interactive computer to a new level.